ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ARTICULATE STORYLINE BAGI DISABILITAS RUNGU PADA PEMBELAJARAN KRIYA KAYU (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this study stems from the absence of instructional media used by woodcraft educators, the underutilization of available facilities, and the lack of experience in developing learning media tailored to the needs of students with hearing disabilities. This research aims to analyze the need for interactive learning media based on Articulate Storyline for students with hearing impairments in woodcraft learning at SLB Negeri 2 Padang. Using a descriptive qualitative method with a Research and Development (R&D) approach focusing on the needs analysis stage the findings reveal that woodcraft learning has been limited to practical activities without theoretical instruction. Both teachers and students expressed the need for media that supports better understanding of woodcraft concepts, such as interactive Articulate Storyline based learning media aligned with multimedia learning theory. The study highlights the importance of developing such media to enhance learning for students with hearing disabilities